Melatonin Ameliorates Hemorrhagic Transformation via Suppression of ROS-Induced NLRP3 Activation after Cerebral Ischemia in Hyperglycemic Rats. (11th March 2021) - Shao, Anwen; Gao, Shiqi; Wu, Haijian; Xu, Weilin; Pan, Yuanbo; Fang, Yuanjian; Wang, Xiaoyu; Zhang, Jianmin
Abstract : Melatonin is a strong antioxidant which beneficially protects against middle cerebral artery occlusion (MCAO) followed by hemorrhagic transformation in rats; protection includes the reduction of neurological deficits, infarction, and hematoma volume. The molecular mechanisms underlying these neuroprotective effects in the MCAO model have not been clearly identified. This study examined the influence and involved mechanism of melatonin on inflammation in hemorrhagic transformation following hyperglycemia MCAO rat model. Compared with the MCAO group, MCAO+dextrose (DX) group showed worse neurological function and higher infarction and hematoma volume. Interestingly, the protein expression of Nod-like receptor protein 3 (NLRP3) inflammasome increased in the MCAO+DX group compared with the MCAO group, which indicated that NLRP3 inflammasome may be involved in the DX-induced hemorrhagic transformation following MCAO. Then, three dosages of melatonin were intraperitoneally injected 2 h after MCAO induction. Melatonin treatment attenuated inflammatory response by inhibiting the reactive oxygen species (ROS) and NLRP3 inflammasome, alleviating neuronal injury, and reducing infarction and hematoma volume, finally improving neurological score. Melatonin also repressed cortical levels of proinflammatory cytokine IL-1 β, which were increased 24 h after hyperglycemia MCAO. In order to identify the potential mechanisms, we further revealed that nigericin administration reversed the neuroprotective effect of melatonin by promoting NLRP3 inflammasome activation. In general, this present study reveals that melatonin prevents the occurrence of hyperglycemia-enhanced hemorrhagic transformation, and this effect might be beneficial to attenuate neurological dysfunction via suppressing the inflammatory response after MCAO which possibly associated with the inhibition of the ROS/NLRP3 inflammasome pathway.